EFEKTIVITAS IMPLEMENTASI KEBIJAKAN PERENCANAAN PEMBANGUNAN DAERAH (Studi Kasus Rencana Kerja Pemerintah Daerah Kota Metro) - Elip Heldan; Malik Malik; Muhammad Ario Pratito (Universitas Bandar Lampung (UBL), 2021)
The problems in this study are: (1) How is the effectiveness of the implementation of the Regional Government Work Plan policy in Metro City?, (2) What are the factors that influence the effectiveness of the Regional Government Work Plan policy implementation in Metro City? This study uses a descriptive research method with a qualitative approach. It aims to find out the facts, symptoms or certain phenomena descriptively with data collection techniques in the form of document review and interviews using interview guide research instruments to several predetermined informants.The results showed that the implementation of the Regional Government Work Plan policy in Metro City was quite effective in terms of the right policy, the right implementation, the right target, the right environment and the right process. The supporting factors for the effectiveness of implementing the Regional Government Work Plan policies in Metro City come from communication and bureaucratic structure, and the inhibiting factors come from resources and dispositions in implementing the Regional Government Work Plans in Metro City.